EFFECTIVENESS ANALYSIS OF MARKETING SYSTEM ANUGERAH MINA LESTARI SMEs USING FACEBOOK SOCIAL MEDIA - Lina Asmara Wati; Hartati Kartikaningsih; Mimit Primyastanto; Supriyadi Supriyadi; Rhytia Ayu Christianty Putri (Journal of Aquaculture and Fish Health, 2020)
This time, in the digital era, a business cannot be separated from digital marketing, this is by the explanation of technological developments. The existence of Small and Medium Enterprises (SMEs) in Indonesia is a driving factor in the creation of national economic development because it can spur economic growth. The high use of social media, especially Facebook in Indonesia, encourages business people to use social media as marketing media. This is also done by Anugerah Mina Lestari  SMEs. So that researchers feel they are researching the Effectiveness of the UKM Mina Lestari Marketing System Using Facebook Social Media. The research used the EPIC Model which involved 80 samples. The sample is part of the population of product buyers from Anugerah Mina Lestari SMEs. The effectiveness of the Anugerah Mina Lestari SME marketing system through Facebook social media that was analyzed using the EPIC Model with four variables (Empathy, Persuasion, Impact, Communication), showed an EPIC Rate of 2.943 which means that the Anugerah Mina Lestari SMEs marketing system through Facebook social media can be assessed effectively.